Exploring the energetic basis of binding of currently used drugs against HIV-1 subtype CRF01_AE protease via molecular dynamics simulations. Issue 16 (2nd November 2021) - Sk, Md Fulbabu; Jonniya, Nisha Amarnath; Kar, Parimal
Abstract: Non-B strains cause nearly 90% of the worldwide human immunodeficiency virus (HIV) infections. At the same time, the protease inhibitors (PIs) were designed for subtype B. Therefore, the use of PIs in the non-B subtype context requires further investigation. Herein, we have investigated the effectiveness of currently used four PIs, namely atazanavir, darunavir, lopinavir, and tipranavir against subtype CRF01_AE (PR CRF ) by employing the MD/MMPBSA (molecular dynamics/molecular mechanics Poisson-Boltzmann surface area) scheme. Our investigation reveals that tipranavir is the most potent inhibitor against PR CRF while the other three PIs display a similar binding affinity. The energetic penalty arises due to the desolvation of polar groups always disfavor the association between PR CRF and PI, and this contribution is the least in the case of tipranavir/PR CRF compared to the other three PI-PR CRF complexes resulting in a better binding affinity for tipranavir. Further, it is revealed that the primary interaction controlling the binding of inhibitors with PR CRF is the van der Waals forces. The dynamic cross-correlation map and principal component analysis show that the anti-correlated motion at the flap region of PR CRF is diminished after the ligand binding. Further, our studies indicate that D25' forms a stable H-bond with darunavir, lopinavir, and tipranavir, while D25 forms a stable H-bond with atazanavir. The per-residue based decomposition of free energy reveals the actual residual origin of the binding free energy and identify the hotspot residues. Overall, the data presented in this study can guide the computer-aided rational design of more potent drugs targetting HIV-1 PR CRF . Communicated by Ramaswamy H. Sarma